Improving learning activities and mathematical reasoning skills for class x students applying problem-based learning - Yuni Haflati Zilda (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Mathematical reasoning abilities and learning activities of MAN 2 Kota Padang students are still low. Several aspects are believed to be the cause of the low reasoning ability, one of which is the monotonous learning model. The purpose of this study was to improve the activity and mathematical reasoning abilities of class X students through a problem-based learning model using the Class Action Research (CAR) method. The research subjects were students of class X IPA 9 MAN 2 Kota Padang, totaling 36 people. The data in this study were collected through student activity observation sheets, mathematical reasoning ability tests carried out at the end of the cycle, practice questions, field notes, videotaping and interviews. The data analysis technique used is descriptive analysis. The results showed that the Problem-Based Learning model could increase student activity but could not significantly improve students' mathematical reasoning abilities. The completeness of the mathematical reasoning ability test results obtained by students at the end of the study only reached 8%, far below the research target of 50%.